The rhizosphere microecological mechanisms of stress-induced quality enhancement in medicinal plants - Xueqian Zhang; Qingsong Ran; Yanfeng Han; Longzhan Gan; Xiao Zou; Chunbo Dong (Plant Stress)
Medicinal plants, a significant category of biological resources with substantial medical and economic value, produce secondary metabolites that exhibit extensive pharmacological activities and important biological functions. These metabolites serve as key indicators for evaluating the quality of medicinal materials. The quality of medicinal materials is closely related to the environment, with those grown under adverse conditions often exhibiting superior quality, a phenomenon known as “stress-induced quality enhancement.” Rhizosphere microorganisms play an essential role in this process. Therefore, in this review, based on existing literature, we explore the mechanisms through which medicinal plants modulate their physiological and metabolic processes via rhizosphere microbiological mechanisms under adverse conditions to enhance the quality of medicinal materials. Specifically, plants subjected to stress increase the production of secondary metabolites, such as phenolic compounds, terpenoids, and alkaloids, to mitigate stress-induced damage. Concurrently, rhizosphere microorganisms promote the synthesis of these secondary metabolites by improving the plant’s antioxidant system, inducing endogenous hormonal responses, participating in nutrient element cycling, regulating the expression of related enzymes and genes, and activating plant immune responses, thereby enhancing the quality of medicinal materials under adverse stress. However, the understanding of these mechanisms remains limited. Thus, we propose several future research directions and suggest that strategies such as genetic breeding, the development of synthetic microbial communities, and the engineering of synthetic ecosystems have the potential to cultivate new varieties of medicinal plants that are high-yielding, of superior quality, and resilient to stress, thereby providing new impetus for the sustainable and healthy development of the medicinal materials industry.